Cumulative impact of axial, structural, and repolarization ECG findings on long-term cardiovascular mortality among healthy individuals in Japan: National Integrated Project for Prospective Observation of Non-Communicable Disease and its Trends in the Aged, 1980 and 1990. (29th August 2020) - Inohara, Taku; Kohsaka, Shun; Okamura, Tomonori; Watanabe, Makoto; Nakamura, Yasuyuki; Higashiyama, Aya; Kadota, Aya; Okuda, Nagako; Murakami, Yoshitaka; Ohkubo, Takayoshi; Miura, Katsuyuki; Okayama, Akira; et al.
Abstract: Aims: Various cohort studies have shown a close association between long-term cardiovascular disease (CVD) outcomes and individual electrocardiographic (ECG) abnormalities such as axial, structural, and repolarization changes. The combined effect of these ECG abnormalities, each assumed to be benign, has not been thoroughly investigated. Methods and Results: Community-dwelling Japanese residents from the National Integrated Project for Perspective Observation of Non-Communicable Disease and its Trends in the Aged, 1980–2004 and 1990–2005 (NIPPON DATA80 and 90), were included in this study. Baseline ECG findings were classified using the Minnesota Code and categorized into axial (left axis deviation, clockwise rotation), structural (left ventricular hypertrophy, atrial enlargement), and repolarization (minor and major ST–T changes) abnormalities. The hazard ratios of the cumulative impacts of ECG findings on long-term CVD death were estimated by stratified Cox proportional hazard models, including adjustments for cohort strata. In all, 16, 816 participants were evaluated. The average age was 51.2 ± 13.5 years; 42.7% participants were male. The duration of follow up was 300, 924 person-years (mean 17.9 ± 5.8 years); there were 1218 CVD deaths during that time. Overall, 4203 participants (25.0%) had one or more categorical ECG abnormalities: 3648 (21.7%) had a single abnormality, and 555 (3.3%) had two or more. The risk of CVD mortality increased as the number of abnormalities accumulated (single abnormality HR 1.29, 95% CI 1.13–1.48; ≥2 abnormalities HR 2.10, 95% CI 1.73–2.53). Conclusions: Individual ECG abnormalities had an additive effect in predicting CVD outcome risk in our large-scale cohort study.